Teaching writing : balancing process and product - Tompkins, Gail E. 4 0 16; 5 (Upper Saddle River, N.J. : Pearson/Merrill Prentice Hall, 2008)
A guide to teaching various forms of writing to K-8 students, covering prewriting, drafting, revising, editing, publishing, idea development, stylistic devices, overcoming obstacles, and other related topics, with a CD covering the major components of workshop, including writing, sharing, and teaching mini-lessons.
System requirements not stated.
Includes bibliographical references (p. 283-290) and indexes.
Professional;Professional
Keywords: 2 -- 0; 6; Composition and exercises;Study and teaching (Elementary);Composition and exercises;Study and teaching. -- English language;Creative writing (Elementary education);English language;Elementary education.;Creative writing.;CD-Roms.; 20; CD-Roms.